Z problematyki ochrony konsumenta w angielskim prawie prywatnym - Sołtysiński, Stanisław (Wydział Prawa i Administracji UAM, 1969)
The paper deals with the problem of the consumer protection under the law of contract and the law of torts. The first part of the article contains basic informations on the consumer movement in the United Kingdom (consumer organizations, the government and the consumer, protective legislation outside the private law). The changes in the attitude towards the consumer are reflected both in legislation and case law. So far as the law of sale is concerned, the traditional common law rule was that there was no legal obligation on the vendor to inform the buyer that he was under a mistake not induced by the act of the seller. The first statutory act that limited the ill consequences of this harsh rule was introduced in 1893. By the Sale of Goods Act a condition is implied that the goods will be reasonably fit for the customers purpose, if the buyer makes known to the seller the purpose for which he requires the goods, so as to show that he relies on the seller's choice, and the goods are of a description which the seller ordinarily supplies. As a rule the consumer's rights against the seller do not extend beyond a cash compensation. There is no doubt that the right for rescission is primarily a consumer's remedy and its limitation by the Sale of Goods Act has evoked sharp criticism among legal writers. Another important statute, the acts governing hire purchase agreements lay down conditions limiting some of ill efects of modern marketing and advertising on the consumer's choice. The most important of these provisions are: the agreement must be in writing; if the contract is made at buyers home he has three days within which he can withdraw; advertisements relating to goods on hire purchase must show full details of the terms, if one or more important figure is shown (such as deposit). One of the latest examples of the evolution on the field of the law of contract is the Misrepresentation Act of 1967. Its main purpose is to give an effective remedy to the person who was induced to contract by some misleading statement. It must be emphasized that the Act has introduced several proposals made by the Commitee on Consumer Protection. The protective legislation has resulted in a widespread use of various forms of exemption clauses by mass producing and marketing enterprisers. These disclaimers of liability usually appear in the printed clauses of standard forms, so called guarantees, on labels attached to goods, etc. In order to protect the consumer the case law seem to recognize the need for developing a number of restrictive rules of construction peculiar to exemption clauses. In earlier times the producer of the manufacture usually sold it to the consumer. Thus the latter, being in privity of contract with the maker, was entitled to sue the producer for losses caused by the defects of the product. The new forms of distribution of goods has changed the legal position of the buyer who is no longer in privity with the producer. Hence courts and legislators are confronted with the problem of finding a satisfactory solution of protecting the legitimate interests of the injured ultimate consumer in cases where he is unable to get recovery from the retailer. Before 1932 it was rather doubtful whether there was any liability on the part of the producer to the ultimate consumer of his product with whom there was no contractual link. But in that year the decision of the House of Lords in the most celebrated case Donoghue v. Stevenson established that the manufacturer of products owes a duty of care to the ultimate consumer or user. The principle has been gradually extended to include repairers, assemblers and builders.
Consumer Protection in English Private Law